Modelling hunter-gatherer settlement patterns : an Australian case study - Pickering, Michael (Oxford : Archaeopress, 2003)
The Garawa Aboriginal people of the southern inland Gulf of Carpentaria, Northern Australia were, until relatively recently, hunter-gatherers. The three principal objectives of this volume are to provide an ethnography of Garawa land-use and settlement.
Includes bibliographical references (p. 199-214).
Keywords: Hunting and gathering societies -- Australia; Aboriginal Australians -- Land tenure; Aboriginal Australians -- Ethnology; Sites - Surveys; Subsistence and economy; Environment - Land management; Social organisation; Garrwa / Garrawa / Garawa people (N155) (NT SE53-08); Environment - Climate and weather - Seasons; Archaeology - Settlement patterns; Gulf of Carpentaria (SD53, SD54, SE54)